Cultura tributaria e informalidad de los comerciantes del mercado modelo de Iquitos, 2023 - Ramírez Núñez, Dessy Pamely (2023)
The study is based on the tax culture that the merchants of the model market have, based on the informality that their businesses have and the lack of tax information that the merchants have, to be able to have a formal company, therefore the study used a methodology Descriptive quantitative, non-experimental cross-sectional design used a population of 20 merchants from the 2023 model market. The study identifies that for the majority of participants the dimensions such as coercion, tax awareness, taxpayer information, access to tax administration services, tax knowledge, cost of formalization and bureaucracy, are perceived as good, the study concludes: that there is a significant relationship between coercion and informality, that there is a significant relationship between tax awareness and informality, that there is a significant relationship between taxpayer information and informality , that there is a significant relationship between access to tax administration services and the informality of merchants in the Modelo market, year 2023.